Food handling practices in houses of Brouwn Healt Centre area of General Pico, La Pampa (Veterinary Science, 2017)
Food-borne diseases are a substantial cause of morbid-mortality and public health problem, producing illness until 20 to 50% of homes. The most vulnerable groups are young, aged, pregnant and immunecompromised people. The objective of the present work was to collect data related to food handling practices at homes and evaluate the impact on health. A descriptive study was conducted from April to July of 2011 in the Brown Health Centre Area of General Pico, La Pampa. The data was collected from a 134 questionnaires to people belonging to kindergarten pupil families, health workers, kindergarten teachers, parents and aged. The results were: 116 (86,5%) inadequate food handling practices, 96 (71,6%) poor hygiene, 57 (42,5%) deficient surface hygiene, 53 (39,5%) poor hygiene cutting board, 47 (35,0%) deficient hands wash, 38 (28,3%) inadequate reheated and 31 (23,1%) food conservation to inadequate temperature. The interviews evidenced not enough knowledge in the aged group about use of detergents, disinfectants, food conservation and not understanding the food packaging label. In conclusion, the healths of the people area were at risk. This study indicates the demand of generation of food safety information
Keywords: Home; Foodborne disease